P654 Monitoring of drug concentrations to predict remission under ustekinumab induction therapy in Crohn's disease patients. (25th January 2019) - Soufflet, N; Boschetti, G; Roblin, X; Cuerq, C; Williet, N; Duclaux Loras, R; Danion, P; Mialon, A; Paul, S; Flourié, B; Nancey, S
Abstract: Background: Ustekinumab, targeting the p40 subunit of interleukin-12 and -23 has been approved for the treatment of moderate to severe Crohn's disease (CD). Predictors of response to this therapy are lacking. We investigated prospectively the usefulness of monitoring faecal calprotectin, serum CRP and ustekinumab concentrations to predict the response to ustekinumab induction therapy in active CD. Methods: All consecutive anti-TNF refractory and active CD patients received an initial i.v. ustekinumab infusion followed by s.c. injections every 8 weeks. Clinical remission, defined as a Harvey–Bradshaw index ≤ 4, was assessed at Week 16. Blood and stool samples were collected at weeks 0, 4, 8, and 16 for measurements of serum CRP, ustekinumab concentrations and faecal calprotectin. Results: Fifty-one patients were included. At Week 16, 32 out of 51 patients (63%) achieved a steroid-free clinical remission. Faecal calprotectin concentrations dropped gradually and significantly over the time between weeks 0 and 16, only in responder patients to ustekinumab induction ( p = 0.006) and not in primary non-responders ( p = 0.36). At Week 8, serum ustekinumab trough levels were significantly higher in responders compared with those in non-responders and was a reliable marker to predict response to induction therapy assessed at week 16 (AUROC = 0.75; sensitivity = 87%; specificity = 66%) with a best cut-off point of 2.0 µg/ml. Conclusions: Ustekinumab induction therapy was effective in two-third of refractory CD patients. Monitoring of serum ustekinumab trough levels at Week 8 is useful to identify responders from non-responders to induction therapy and may contribute to the clinician's decision-making to adapt further the therapeutic strategies.